2020
DOI: 10.1123/ijspp.2019-0554
|View full text |Cite
|
Sign up to set email alerts
|

Warming Up Before a 20-Minute Endurance Effort: Is It Really Worth It?

Abstract: Purpose: To analyze the effects of different warm-up protocols on endurance-cycling performance from an integrative perspective (by assessing perceptual, neuromuscular, physiological, and metabolic variables). Methods: Following a randomized crossover design, 15 male cyclists (35 [9] y; peak oxygen uptake [VO2peak] 66.4 [6.8] mL·kg−1·min−1) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…8 In this study, it was found that a short, specific WU elicited similar physiological responses, perception of effort and subsequent sprint time-trial performance compared to a longer, more traditional approach. This is, in part, consistent with previous research acknowledging the potential for longerduration WUs to result in fatigue, 6,[8][9][10][11] while shorter WUs have been reported to enhance physiological and/or performance measures in rowing 6 and track cycling. 11 While the aforementioned study investigated WU approaches in sprint XC skiing, no research has been conducted to date on WU strategies prior to distance XC skiing.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…8 In this study, it was found that a short, specific WU elicited similar physiological responses, perception of effort and subsequent sprint time-trial performance compared to a longer, more traditional approach. This is, in part, consistent with previous research acknowledging the potential for longerduration WUs to result in fatigue, 6,[8][9][10][11] while shorter WUs have been reported to enhance physiological and/or performance measures in rowing 6 and track cycling. 11 While the aforementioned study investigated WU approaches in sprint XC skiing, no research has been conducted to date on WU strategies prior to distance XC skiing.…”
Section: Introductionsupporting
confidence: 90%
“…Muscle activation and priming of the upper-and lower-body musculature did not form part of the skiers' WU strategies, despite recent work indicating that brief (10-s) high-intensity sprints within a WU may elicit potentiating effects on both V̇O2 kinetics and neuromuscular qualities. 9 In fact, only five of the 21 skiers (three women, two men) planned any type of muscleactivation exercises (e.g., countermovement jumps or exercises using external resistance, such as bands). Prior to both the distance and sprint events, 11 skiers (eight women, three men) planned "high-intensity skiing", with individual descriptions including "short sprints" and "sprints on skis".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, to date, there is still limited evidence with these athletes [26,32,47]. of note, considering the transient duration of PAPE (up to 10 minutes after CAs), it is still to be solved if the pacing improvements during the first splits of an endurance test may affect the total time, which may be related to the duration of the endurance exercise [48][49][50]. In addition, more studies comparing the effect of different warm-up protocols on both PAPE and cardiometabolic responses are needed, as endurance performance can be also related to oxygen uptake kinetics and perceptual responses [19].…”
Section: Warm-upmentioning
confidence: 99%
“…The likely to very likely improvement in CMJ performance following ACT and COM compared to PAS may be related to the inclusion of the 5 weighted CMJs at the end of the active warm-up, which were used to induce a PAP response (ie, an increase in muscle force after a conditioning contractile activity, such as a series of maximal or near-maximal dynamic exercises) 24,25 . The significant improvement in CMJ performance for COM compared to PAS (∼6.8%), but not for ACT compared to PAS (∼2.9%), suggests a potential benefit of supplementary passive heating either during and/or after the weighted CMJs in addition to the active warm-up used in the current study.…”
Section: Discussionmentioning
confidence: 99%